Solder resist ink and a solder resist dry film having high b-hast reliability and a method of manufacturing the same
Patent Information
- Application Number
- CN202610798790.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-09
AI Technical Summary
但该技术方案未针对B-HAST严苛工况进行体系设计,既未对树脂本体疏水改性以降低固化膜吸湿率,也未引入离子捕捉与界面水阻隔功能组分,在高温高湿、直流偏压条件下,固化膜易因吸湿、卤素与铜离子迁移引发电化学失效,绝缘电阻快速下降,还存在界面分层开裂风险,无法满足高端封装基板对阻焊干膜长期高可靠性的使用需求,开发兼具优异基础工艺性能与高B-HAST可靠性的阻焊干膜,成为本领域亟待解决的技术问题
1.本发明通过限定特定阻焊油墨的组分,使得以该油墨制备的阻焊干膜在130℃、85%RH,施加直流偏压的严苛条件下,可延长绝缘电阻下降至1×106Ω以下的失效时间,且不出现分层开裂现象。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of solder resist ink technology, specifically to solder resist ink and a high B-HAST reliability solder resist dry film and its preparation method. Background Technology
[0002] As the electronics and information industry develops towards higher density, higher integration, and higher reliability, the linewidth and spacing of printed circuit boards and IC packaging substrates are becoming increasingly refined. This places far greater demands on the damp heat aging and insulation reliability of solder resist, the core material for circuit protection, than on traditional indicators. B-HAST (High Accelerated Temperature and Humidity Stress Test) is a core method for evaluating the long-term service performance of solder resist layers under harsh damp heat and bias conditions. Its results directly determine the service life of high-end electronic devices and have become a key performance indicator for solder resist materials used in high-end packaging substrates.
[0003] Current commercially available and publicly available solder resist dry film technologies mainly focus on optimizing basic properties such as development resolution, substrate adhesion, solder resistance, and chemical resistance, while paying insufficient attention to the insulation failure problem under high temperature and high humidity DC bias. Chinese invention patent application CN121554634A discloses a film-forming resin and the solder resist dry film prepared therefrom. By grafting and modifying acrylic resin with photosensitive molecules containing double-bonded isocyanates, the development accuracy, mechanical strength, and chemical resistance of the dry film are optimized, and the resolution can be improved to below 50μm, meeting the basic processing requirements of fine circuits. However, this technical solution is not designed for the harsh operating conditions of B-HAST. It does not modify the resin body to be hydrophobic to reduce the moisture absorption rate of the cured film, nor does it introduce functional components for ion capture and interfacial water barrier. Under high temperature, high humidity and DC bias conditions, the cured film is prone to electrochemical failure due to moisture absorption, halogen and copper ion migration, resulting in a rapid decrease in insulation resistance. There is also a risk of interfacial delamination and cracking. It cannot meet the long-term high reliability requirements of high-end packaging substrates for solder resist dry films. Developing solder resist dry films that combine excellent basic process performance and high B-HAST reliability has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] The first aspect of the present invention provides a solder resist ink, which, by weight, comprises: 30-50 parts of alkali-soluble photosensitive resin, 10-25 parts of thermosetting resin, 10-20 parts of photopolymerizable monomer, 1-5 parts of photoinitiator, 15-30 parts of hydrophobic inorganic filler, 1-5 parts of ion scavenger, and 20-40 parts of organic solvent.
[0005] In existing technologies, dry resist films only improve the resistance to damp heat by modifying a single resin, without forming a synergistic protection system of moisture absorption barrier and ion migration inhibition. Under the harsh conditions of 130℃, 85%RH and DC bias applied by B-HAST, they are prone to rapid failure due to water molecule penetration and swelling, and rapid electrochemical migration of metal ions, resulting in a sharp drop in insulation resistance and film delamination and cracking. This invention constructs a triple synergistic protection system of "resin body hydrophobicity - interface path barrier - migrating ion capture" by precisely limiting the ratio range of each core component of the solder resist ink: 30-50 parts of hydrophobically modified alkali-soluble photosensitive resin serve as the core film-forming matrix, which can significantly reduce the intrinsic moisture absorption rate of the resin body and avoid the attenuation of insulation performance caused by resin swelling under high temperature and high humidity conditions from the source; 10-25 parts of thermosetting resin form a dense interpenetrating cross-linked network with the photocuring system after thermosetting. Its rigid aromatic ring and heterocyclic structure can further improve the cross-linking density and reduce the internal stress of curing, which not only greatly extends the penetration path of water molecules, but also fundamentally inhibits the film layer delamination and cracking phenomenon under humid and hot alternating environment. 10-20 parts of photopolymerizable monomers and 1-5 parts of photoinitiator are synergistically matched to precisely control the photocuring rate and crosslinking network uniformity, reducing water molecule penetration channels caused by curing defects; 15-30 parts of hydrophobically surface-modified inorganic fillers can uniformly fill the microscopic voids in the resin matrix, forming an interfacial synergistic barrier effect with the hydrophobically modified resin, further blocking the penetration path of water molecules; 1-5 parts of ion scavenger, through a unique layered ion exchange structure, can actively capture free migrating halide anions and copper ions dissolved from copper circuits in the system under humid and hot bias conditions, blocking the formation of electrochemical migration conductive channels from the root, ultimately achieving an insulation resistance reduction to 1×10 under the harsh conditions of B-HAST. 6 The failure time below Ω is significantly extended, while the occurrence of film delamination and cracking during the test is completely avoided.
[0006] The alkali-soluble photosensitive resin includes a carboxyl-modified epoxy acrylate resin with an acid value of 40-80 mg KOH / g and a weight-average molecular weight of 8000-30000.
[0007] Optionally, the raw materials for preparing the alkali-soluble photosensitive resin include one or more of fluorine-containing monomers or silicon-containing monomers.
[0008] The thermosetting resin includes a thermosetting epoxy resin, wherein the epoxy equivalent of the thermosetting epoxy resin is 150-500 g / eq.
[0009] The thermosetting epoxy resin is selected from one or more of bisphenol A type epoxy resin, phenolic epoxy resin, naphthalene-containing epoxy resin, and triglycidyl isocyanurate.
[0010] Optionally, the thermosetting resin includes a naphthalene-containing epoxy resin and triglycidyl isocyanurate, wherein the weight ratio of the naphthalene-containing epoxy resin and triglycidyl isocyanurate is 1:(0.5-1.5).
[0011] The rigid planar structure of naphthalene rings in naphthalene-containing epoxy resins can effectively reduce the water absorption rate of the cured film and improve its resistance to damp heat.
[0012] The photopolymerizable monomer is selected from one or more of trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, and ethoxylated bisphenol A diacrylate.
[0013] Optionally, the photopolymerizable monomers include pentaerythritol hexaacrylate and ethoxylated bisphenol A diacrylate, wherein the weight ratio of pentaerythritol hexaacrylate to ethoxylated bisphenol A diacrylate is 1:(0.5-1).
[0014] The photoinitiator is selected from one or more of α-hydroxy ketone photoinitiators, acylphosphine oxide photoinitiators, benzophenone and its derivatives.
[0015] The hydrophobic inorganic filler is selected from one or more of the following: fused silica surface-treated with silane coupling agent, hydrophobic fumed silica, barium sulfate, and talc, with an average particle size of 0.2-2.0 μm.
[0016] The silane coupling agent includes one or more of fluorinated silane coupling agents or phenyl silane coupling agents.
[0017] The ion scavenger is selected from one or more of hydrotalcite compounds, zirconium-based inorganic ion exchangers, and bismuth-based ion scavengers.
[0018] Optionally, the ion scavenging agent is selected from hydrotalcite compounds.
[0019] Optionally, the hydrotalcite compounds include Mg-Al type hydrotalcite.
[0020] The ion trap has a layered anion exchange structure, which can effectively capture halide ions migrating in the solder resist film and copper ions dissolved from copper circuits in the B-HAST test, thereby inhibiting the occurrence of electrochemical migration in the solder resist dry film from the source.
[0021] The organic solvent is selected from one or more of propylene glycol methyl ether acetate, butanone, cyclohexanone, and ethyl acetate.
[0022] Optionally, the solder resist ink may further comprise 0.5-3 parts by weight of a thermosetting accelerator and 0.5-2 parts by weight of an additive.
[0023] The thermosetting accelerator includes one or more of dicyandiamide, imidazole compounds, and boron trifluoride amine complexes.
[0024] The additives include one or more of leveling agents and defoamers.
[0025] Optionally, the viscosity of the solder resist ink is 2200 mPa·s (25°C).
[0026] A second aspect of the present invention provides a solder resist dry film, comprising a carrier film, a solder resist functional layer and a protective film stacked sequentially, wherein the solder resist functional layer comprises solder resist ink.
[0027] The thickness of the solder resist functional layer is 20-50 μm.
[0028] The third aspect of the present invention provides a method for preparing a solder resist dry film, comprising the following steps: coating solder resist ink onto a carrier film, drying it to form a solder resist functional layer on the surface of the carrier film, and attaching a protective film to the surface of the solder resist functional layer to obtain a solder resist dry film.
[0029] Beneficial effects 1. This invention, by defining the components of a specific solder resist ink, enables the solder resist dry film prepared with this ink to maintain an insulation resistance reduction to 1×10⁻⁶ under harsh conditions of 130°C, 85%RH, and applied DC bias. 6 Failure time below Ω, and no delamination or cracking occurs.
[0030] 2. By limiting the raw materials for preparing the alkali-soluble photosensitive resin to include one or more of fluorine-containing monomers or silicon-containing monomers, the present invention can enable the adhesion of the solder resist dry film to reach grade 5B and the saturated water absorption rate to ≤1.5%.
[0031] 3. By limiting the hydrophobic inorganic filler to be treated with a silane coupling agent, the present invention can further extend the B-HAST failure time of the solder resist dry film by ≥100h.
[0032] 4. By specifying that the thermosetting resin is a compound of naphthalene-containing epoxy resin and triglycidyl isocyanurate in a weight ratio of 1:(0.5-1.5), the present invention can balance the water absorption rate and damp heat resistance of the solder resist dry film, while the B-HAST failure time is ≥300h.
[0033] 5. By limiting the ion scavenger to one or more of hydrotalcite compounds, zirconium-based inorganic ion exchangers, and bismuth-based ion scavengers, this invention can effectively suppress the occurrence of electrochemical migration in solder resist dry films. Detailed Implementation
[0034] Example 1 A solder resist ink, by weight, comprises: 45 parts of alkali-soluble photosensitive resin (solution form, solid content 60wt%), 15 parts of thermosetting resin (naphthalene ring epoxy resin, epoxy equivalent 220g / eq, Shanghai Huayi Resin Co., Ltd. EBA-65), 13 parts of photopolymerizable monomer (8 parts of dipentaerythritol hexaacrylate + 5 parts of ethoxylated bisphenol A diacrylate), 3 parts of photoinitiator (2 parts Irgacure 907 + 1 part ITX), and hydrophobic inorganic filler (hydrophobic fused silica, surface-treated with phenylsilane coupling agent, average particle size 0.5μm; substrate fused silica: Tatsumori Ltd. JY-50; coupling agent phenylsilane treatment agent: Dow Corning DOWSIL Z-9805). 20 parts Silane, 3 parts ion capture agent (Mg-Al type hydrotalcite), 30 parts organic solvent (propylene glycol methyl ether acetate), 1.5 parts thermosetting accelerator (dicyandiamide), 0.5 parts leveling agent, and 0.5 parts defoamer.
[0035] The synthesis of the alkali-soluble photosensitive resin comprises the following steps: In a four-necked flask equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet tube, 100 parts by weight of bisphenol A type epoxy resin (epoxy equivalent 186 g / eq), 72 parts by weight of acrylic acid, 0.2 parts by weight of hydroquinone, and 0.5 parts by weight of triphenylphosphine are added. The mixture is heated to 100°C under nitrogen protection and reacted until the acid value is ≤5 mg KOH / g. The temperature is then lowered to 80°C, and 38 parts by weight of tetrahydrophthalic anhydride and 10 parts by weight of fluorinated acrylate monomer (hexafluorobutyl methacrylate) are added. The reaction continues until the acid value reaches 55-60 mg KOH / g. Propylene glycol methyl ether acetate is added to dilute the mixture to a solid content of 60 wt%, yielding an alkali-soluble photosensitive resin with a weight-average molecular weight of 16000.
[0036] The preparation method of the solder resist ink includes the following steps: adding alkali-soluble photosensitive resin to thermosetting resin, photopolymerizable monomer, photoinitiator, hydrophobic inorganic filler, ion scavenger, thermosetting accelerator, leveling agent, defoamer, and organic solvent and mixing them; dispersing them in a high-speed disperser at 2000 rpm for 30 min; and obtaining a solder resist ink with a viscosity of 1800 mPa·s (25℃) after vacuum degassing.
[0037] A solder resist dry film is composed of a carrier film, a solder resist functional layer and a protective film stacked sequentially, wherein the solder resist functional layer includes solder resist ink.
[0038] A method for preparing a solder resist dry film includes the following steps: solder resist ink is uniformly coated onto a 25μm thick PET carrier film using a slot coater, dried in a 100℃ oven for 5 minutes to form a 35μm thick solder resist functional layer, a 30μm thick PE protective film is laminated onto the surface of the solder resist functional layer, and then the film is wound up to obtain the solder resist dry film.
[0039] Example 2 The specific implementation method is the same as in Example 1; the difference is that in the synthesis of the alkali-soluble photosensitive resin, 10 parts by weight of the fluorinated acrylate monomer is replaced with 12 parts by weight of the silicone acrylate monomer (3-(trimethoxysilyl)propyl acrylate); the ion scavenger is replaced with 4 parts of bismuth-based ion scavenger (ZB286 of Linyi Lanshan District Hengkang Environmental Protection Technology Co., Ltd.).
[0040] Example 3 The specific implementation method is the same as in Example 1; the difference is that the hydrophobic inorganic filler is replaced with: 8 parts of hydrophobic fumed silica (average particle size 0.2 μm) + 12 parts of fused silica treated with phenylsilane; the ion scavenger is replaced with: 2 parts of Mg-Al type hydrotalcite + 2 parts of zirconium-based ion exchanger (Huiya New Materials Co., Ltd. IXE-100).
[0041] Example 4 The specific implementation method is the same as in Example 1; the difference is that the solder resist ink, by weight, comprises: 40 parts of alkali-soluble photosensitive resin (solution form, solid content 60wt%), 18 parts of thermosetting resin, 12 parts of photopolymerizable monomer (dipentaerythritol hexaacrylate), 3 parts of photoinitiator (Irgacure 819), 25 parts of hydrophobic inorganic filler (molten silica surface-treated with perfluorodecyltrimethoxysilane, average particle size 0.3μm), 4 parts of ion scavenger (Mg-Al type hydrotalcite), 25 parts of organic solvent (propylene glycol methyl ether acetate), 1 part of thermosetting accelerator (dicyandiamide), and 0.8 parts of leveling agent.
[0042] The viscosity of the solder resist ink is 2200 mPa·s (25℃).
[0043] The thermosetting resin comprises 10 parts of naphthyl ring epoxy resin (epoxy equivalent 195 g / eq, Shanghai Huayi Resin Co., Ltd. EBA-65) and 8 parts of triglycidyl isocyanurate.
[0044] Comparative Example 1 The specific implementation method is the same as in Example 1; the difference is that the solder resist ink component in Comparative Example 1 does not contain an ion scavenger.
[0045] Comparative Example 2 The specific implementation method is the same as in Example 1; the difference is that the hydrophobic inorganic filler in Comparative Example 2 is: molten silica (without silane coupling agent surface treatment, average particle size 0.5 μm).
[0046] Comparative Example 3 The specific implementation method is the same as in Example 1; the difference is that no fluorinated acrylate monomer is added during the synthesis of the alkali-soluble photosensitive resin in Comparative Example 3; the prepared alkali-soluble photosensitive resin has an acid value of 58 mgKOH / g and a weight-average molecular weight of 15000.
[0047] Performance testing methods The solder resist dry films prepared in each embodiment and comparative example were respectively attached to copper-clad laminates with comb-shaped electrode patterns (line width / line spacing = 50 μm / 50 μm). After exposure, development, and thermal curing (150℃ × 60 min), solder resist test samples were obtained. Performance tests were performed according to the following items, and the test data are listed in Table 1: 1. B-HAST Reliability Test According to JESD22-A110 standard, the test conditions were: temperature 130℃, relative humidity 85%, with a 5V DC bias applied between adjacent comb electrodes. An online insulation resistance monitoring system was used to continuously record the insulation resistance value between the comb electrodes. The test was conducted when the insulation resistance decreased to 1×10⁻⁶. 6 The failure criterion is Ω or less, and the time elapsed from the start of the test to failure is recorded as the "B-HAST failure time". At the same time, the surface and cross-sectional morphology of the solder resist layer are observed by optical microscopy and SEM (scanning electron microscopy) to determine whether delamination, cracking or electrochemical migration occurred during the test.
[0048] 2. Saturated water absorption rate The cured solder mask was peeled off from the substrate and placed at 85℃ / 85%RH for 168 hours. The rate of change in quality was then measured.
[0049] 3. Adhesion Adhesion rating was assessed according to ASTM D3359 standard using the cross-cut adhesion test, based on the IPC-TM-650 method.
[0050] 4. Resistance to solder heat Immerse the sample in molten solder at 288°C for 10 seconds, repeat 3 times, and observe whether the solder mask layer shows blistering, peeling or discoloration.
[0051] Table 1
[0052] As shown in Table 1 above, the insulation resistance of the solder resist dry film of Examples 1-4 of the present invention decreased to 1×10⁻⁴ under the harsh conditions of B-HAST. 6 The failure time for all samples below Ω exceeded 200 hours, with Example 4 reaching 312 hours, and no delamination cracking was observed during the test.
[0053] Comparative Example 1, which does not contain an ion trap, still had a significantly shorter B-HAST failure time (72h) than Example 1 (256h) despite the use of a hydrophobic resin system to reduce the saturated water absorption rate. This indicates that the ion trap plays a crucial role in inhibiting electrochemical migration and extending the failure time.
[0054] In Comparative Example 2, after replacing the hydrophobic filler with ordinary filler, the saturated water absorption rate increased to 2.0%, and the B-HAST failure time was shortened to 48 hours, which confirmed the importance of hydrophobic inorganic fillers in blocking water molecules from penetrating along the filler-resin interface and delaying failure.
[0055] Comparative Example 3 used an unmodified alkali-soluble resin, and its failure time (95h) was between that of Comparative Example 1 and Example 1, indicating that the hydrophobic modification of the resin body and the hydrophobic treatment of the filler have a synergistic effect, which together extend the service life of the solder resist dry film under B-HAST conditions.
[0056] Example 4 further reduced water absorption and increased crosslinking density by introducing finer particle size fillers treated with perfluorosilane and thermosetting resin, thus achieving the longest B-HAST failure time.
[0057] In terms of conventional process performance, the adhesion of each embodiment reached level 5B, and the solder heat resistance passed the test, indicating that the present invention achieves high B-HAST reliability without compromising the basic process applicability of the solder resist dry film.
[0058] In summary, this invention successfully achieves a balance between high reliability and other key process performance of B-HAST through the synergistic effect of the various functional components in the formulation.
Claims
1. A solder resist ink, characterized in that, By weight, the components include: 30-50 parts of alkali-soluble photosensitive resin, 10-25 parts of thermosetting resin, 10-20 parts of photopolymerizable monomer, 1-5 parts of photoinitiator, 15-30 parts of hydrophobic inorganic filler, 1-5 parts of ion scavenger, and 20-40 parts of organic solvent.
2. The solder resist ink according to claim 1, characterized in that, The alkali-soluble photosensitive resin includes a carboxyl-modified epoxy acrylate resin with an acid value of 40-80 mg KOH / g and a weight-average molecular weight of 8000-30000.
3. The solder resist ink according to claim 2, characterized in that, The raw materials for preparing the alkali-soluble photosensitive resin include one or more of fluorine-containing monomers or silicon-containing monomers.
4. The solder resist ink according to claim 1, characterized in that, The thermosetting resin includes a thermosetting epoxy resin, wherein the epoxy equivalent of the thermosetting epoxy resin is 150-500 g / eq.
5. The solder resist ink according to claim 4, characterized in that, The thermosetting resin includes a naphthalene-containing epoxy resin and triglycidyl isocyanurate, wherein the weight ratio of the naphthalene-containing epoxy resin and triglycidyl isocyanurate is 1:(0.5-1.5).
6. The solder resist ink according to claim 1, characterized in that, The ion scavenger is selected from one or more of hydrotalcite compounds, zirconium-based inorganic ion exchangers, and bismuth-based ion scavengers.
7. The solder resist ink according to claim 1, characterized in that, The hydrophobic inorganic filler is treated with a silane coupling agent.
8. A solder resist dry film, characterized in that, It comprises a carrier film, a solder resist functional layer and a protective film stacked in sequence, wherein the solder resist functional layer comprises the solder resist ink as described in any one of claims 1-7.
9. The solder resist dry film according to claim 8, characterized in that, The thickness of the solder resist functional layer is 20-50 μm.
10. A method for preparing a solder resist dry film according to claim 9, characterized in that, Includes the following steps: Solder resist ink is coated onto the surface of a carrier film, and after drying, a solder resist functional layer is formed on the surface of the carrier film. A protective film is then attached to the surface of the solder resist functional layer to obtain a dry solder resist film.
Citation Information
Patent Citations
Film-forming resin and preparation method thereof, resin composition and solder resist dry film
CN121554634A